Pengaruh Pendidikan Kesehatan Pengendalian Kolesterol terhadap Kadar Kolesterol dalam Darah - Indrawati, Iin; Hesty, Hesty; Maimaznah, Maimaznah (Prosiding Seminar Kesehatan Nasional, 2023)
Cholesterol levels in the blood contribute to the occurrence of myocardial infarction. According to the World Health Organization, more than 7 million people died from myocardial infarction throughout the world in 2002. The aim of this research was to see the effect of health education about controlling cholesterol on blood cholesterol levels. This research is a quantitative study with a pre-experiment design with a pretest - posttest design approach with one group to see differences in respondents' cholesterol levels before and after the intervention. The population of this study were residents of Talang Banjar Village, Jambi City, especially women from the gymnastics group on Rts 29 and 30, totaling 35 people. Sample selection used total sampling technique. The results of this study show that there is no difference in people's cholesterol levels before and after health education on cholesterol control with a p-value of 0.889 > 0.05. It would be best to carry out further research on other factors that influence health behavior. It is important to have the participation of local government officials in collaboration with the community health center in the Talang Banjar sub-district working area to continue to provide cholesterol prevention and control measures as well as carry out routine cholesterol screening. For the government in the Talang Banjar sub-district, this data can be used as a guide in making policies for determining regional programs. Research outputs are published in accredited national journals.Â